2009
DOI: 10.1073/pnas.0903809106
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways guide oxygen diffusion into flavoenzyme active sites

Abstract: Dioxygen (O2) and other gas molecules have a fundamental role in a variety of enzymatic reactions. However, it is only poorly understood which O2 uptake mechanism enzymes employ to promote efficient catalysis and how general this is. We investigated O2 diffusion pathways into monooxygenase and oxidase flavoenzymes, using an integrated computational and experimental approach. Enhanced-statistics molecular dynamics simulations reveal spontaneous protein-guided O2 diffusion from the bulk solvent to preorganized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
172
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 46 publications
(56 reference statements)
12
172
1
Order By: Relevance
“…A positive charge around the flavin reaction site, which can be provided by amino acid residues [15,26,[29][30][31][32] or bound substrate and/or product [33][34][35][36], can influence this. Channels leading from the surface to the active site may affect oxidase reactivity [37,38]. Altering the oxygen reactivity is of considerable interest as shown in recent reviews [15,28] and works of Krondorfer et al [39], Sygmund et al [40], Leferink et al [41], and others [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…A positive charge around the flavin reaction site, which can be provided by amino acid residues [15,26,[29][30][31][32] or bound substrate and/or product [33][34][35][36], can influence this. Channels leading from the surface to the active site may affect oxidase reactivity [37,38]. Altering the oxygen reactivity is of considerable interest as shown in recent reviews [15,28] and works of Krondorfer et al [39], Sygmund et al [40], Leferink et al [41], and others [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] More recent work found that O 2 follows specific tunnels (see above), [35][36][37] may involve multiple pathways, and is likely to be coupled (slaved) to the protein motion. [38][39][40][41][42] The possibility for a ligand to follow multiple pathways was, for example, demonstrated experimentally and through MD simulation for CO in Mb and O 2 -migration in flavoenzymes. 38,43,44 The studies also suggest that small ligands can move through the bulky regions of the protein governed by thermal fluctuations of the protein and that ligand migration follows defined routes through the protein matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42] The possibility for a ligand to follow multiple pathways was, for example, demonstrated experimentally and through MD simulation for CO in Mb and O 2 -migration in flavoenzymes. 38,43,44 The studies also suggest that small ligands can move through the bulky regions of the protein governed by thermal fluctuations of the protein and that ligand migration follows defined routes through the protein matrix. 42,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Multiple pathways and active migration make a kinetic analysis of the ligand dynamics particularly relevant in view of the different time scales involved.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recent developments in efficient computational sampling methods have allowed thorough scanning of the possible pathways for gas diffusion in the interior of proteins. [26][27][28][29] For example, such computational investigations have proved useful in understanding gas diffusion in many protein systems such as molecular dioxygen pathways via dynamic oxygen access channels in flavoproteins, [30][31][32] ammonia transport in carbamoyl phosphate synthetase, [33][34][35] and gas diffusion and channeling in hemoglobin. 28,36 In this paper, we use explicit solvent all-atom molecular dynamics (MD) simulations to investigate the protein barrel fluctuations in mCherry, which is one of the most useful monomeric variants of RFP.…”
Section: Introductionmentioning
confidence: 99%